“Stratificazioni” nello spazio antropico; per una dialettica tra storia e contemporaneità (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
If urban-territorial facts are complex in expressing the values of architecture and the environment, there is no doubt that their identification is the natural premise of any defense action, and it can certainly be said that design issues claim to pay special attention to the ways through which the dialectic between pre-existences is brought into being. The topic concerns the relationship between the architecture of the past and the architecture of the present; a theme that postulates a planning process capable of satisfying both the reasons of history and the needs of contemporaneity. The whole theme revolves around this dialectic; hence the need for a critical approach to be traced back to the propositional interests of the intervention. Key words: city, history, contemporaneity.